Molecular analysis of inherited disorders of cornification in polish patients show novel variants and functional data and provokes questions on the significance of secondary findings - Katarzyna Wertheim-Tysarowska; Katarzyna Osipowicz; Katarzyna Woźniak; Justyna Sawicka; Adrianna Mika; Anna Kutkowska-Kaźmierczak; Katarzyna Niepokój; Agnieszka Sobczyńska-Tomaszewska; Bartłomiej Wawrzycki; Aldona Pietrzak; Robert Śmigiel; Bartosz Wojtaś; et al. (Orphanet Journal of Rare Diseases)
Abstract Background The Mendelian Disorders of Cornification (MeDOC) comprise a large number of disorders that present with either localised (palmoplantar keratoderma, PPK) or generalised (ichthyoses) signs. The MeDOC are highly heterogenic in terms of genetics and phenotype. Consequently, diagnostic process is challenging and before implementation of the next generation sequencing, was mostly symptomatic, not causal, which limited research on those diseases. The aim of the study was to genetically characterise a cohort of 265 Polish patients with MeDOC and to get insight into the skin lesions using transcriptome and lipid profile analyses. Results We detected causal variants in 85% (226/265) patients. In addition to the primary gene defect, a pathogenic variant in another gene involved in MeDOC pathology was identified in 23 cases. We found 150 distinct variants in 33 genes, including 32 novel and 16 recurrent (present in > 5 alleles). In 43 alleles large rearrangements were detected, including deletions in the STS, SPINK5, CERS3 and recurrent duplication of exons 10–14 in TGM1. The RNA analysis using samples collected from 18 MeDOC patients and 22 controls identified 1377 differentially expressed genes - DEG. The gene ontology analysis revealed that 114 biological processes were upregulated in the MeDOC group, including i.e. epithelial cell differentiation, lipid metabolic process; homeostasis; regulation of water loss via skin; peptide cross-linking. The DEG between TGM1 and ALOX12B patients, showed that RNA profile is highly similar, though fatty acid profile in epidermal scrapings of those patients showed differences e.g. for the very long chain fatty acids (VLCFAs; FAs ≥ C20), the very long-chain monounsaturated fatty acids (VLC-MUFAs, FAs ≥ C20:1) and the n6 polyunsaturated fatty acids (n6 PUFAs). Conclusion Our results show that NGS-based analysis is an effective MeDOC diagnostic tool. The Polish MeDOC patients are heterogenic, however recurrent variants are present. The novel variants and high number of TGM1 and SPINK5 copy number variations give further insight into molecular pathology of MeDOC. We show that secondary variants in MeDOC-related genes are present in a significant group of patients, which should be further investigated in the context of phenotype modifiers. Finally, we provide novel RNA and lipid data that characterise molecularly MeDOC epidermis.